2014
DOI: 10.1016/j.jim.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Development of a suspension array assay in multiplex for the simultaneous measurement of serum levels of four eosinophil granule proteins

Abstract: The concentrations of major basic protein (MBP), eosinophil cationic protein (ECP), eosinophil derived neurotoxin (EDN) and eosinophil peroxidase (EPO) have been associated with eosinophilic disease severity. Whereas a variety of techniques have been used to measure individual eosinophil granule protein concentration, none of these methods efficiently measures MBP, ECP, EDN and EPO simultaneously. A multiplex suspension array system was developed to simultaneously measure the concentration of MBP, ECP, EDN and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…Serum levels of eosinophil granule proteins, cytokines, and chemokines were measured by suspension array multiplex immunoassays, using a previously described assay [12] and Millipore kits (Milliplex MAP Human T-Helper 17 Cytokine Panel and Cytokine/Chemokine Panels I and II, EMD Millipore). Specific mediators measured and minimal detectable levels are given in the Supplementary Data.…”
Section: Serum Mediator Analysismentioning
confidence: 99%
“…Serum levels of eosinophil granule proteins, cytokines, and chemokines were measured by suspension array multiplex immunoassays, using a previously described assay [12] and Millipore kits (Milliplex MAP Human T-Helper 17 Cytokine Panel and Cytokine/Chemokine Panels I and II, EMD Millipore). Specific mediators measured and minimal detectable levels are given in the Supplementary Data.…”
Section: Serum Mediator Analysismentioning
confidence: 99%
“…Eosinophils show the highest inflammatory activity when GM-CSF is released. Makiya et al reported that the eosinophil count and the CD69 expression correlated with the granule protein concentration [10]. Liapis et al showed that activated eosinophils contributed to thrombotic microangiopathy (TMA) [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since blood eosinophil numbers do not necessarily indicate the extent of eosinophil involved in the affected tissues, eosinophilic tissue infiltration and end-organ manifestations can occur in the absence of peripheral eosinophilia [5]. In such cases, measurement of eosinophil granule proteins in serum, sputum, or other body fluids can help to monitor the disease activity [7].…”
Section: Discussionmentioning
confidence: 99%